2015
DOI: 10.1016/j.humov.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of “Deficits of hot executive function in developmental coordination disorder: Sensitivity to positive social cues”

Abstract: Recent research shows that children with motor coordination problems (or developmental coordination disorder--DCD) show deficits in not only cool executive function (EF), but also hot EF. We aimed to determine whether this deficit of hot EF is due to heightened sensitivity to rewarding stimuli, specifically, or to a general deficit of cognitive control, like inhibition. Using two versions of a go/no-go task, one with neutral facial expressions and the other with happy and fearful faces, we compared 12 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 71 publications
(93 reference statements)
1
7
0
1
Order By: Relevance
“…He et al (2018) reported that adults with DCD performed poorly in the Go/Nogo task compared to adults with typical development (TD). Identical results were obtained for other inhibition tasks such as emotional face Go/Nogo task (Rahimi-Golkhandan et al, 2016;Rahimi-Golkhandan et al, 2015), the stop signal task (He et al, 2018), the Simon task (Mandich et al, 2002), and the Stroop task (Pratt et al, 2014). These results indicated that motor clumsiness decreases the performance of inhibition tasks.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…He et al (2018) reported that adults with DCD performed poorly in the Go/Nogo task compared to adults with typical development (TD). Identical results were obtained for other inhibition tasks such as emotional face Go/Nogo task (Rahimi-Golkhandan et al, 2016;Rahimi-Golkhandan et al, 2015), the stop signal task (He et al, 2018), the Simon task (Mandich et al, 2002), and the Stroop task (Pratt et al, 2014). These results indicated that motor clumsiness decreases the performance of inhibition tasks.…”
supporting
confidence: 54%
“…In previous studies, children with DCD committed more errors in the context of the Nogo stimulus of happy face than children with TD did, but no difference was found for the Nogo stimuli of neutral, sad, and fearful faces (Rahimi-Golkhandan et al, 2016;Rahimi-Golkhandan et al, 2015). This finding suggested that children with DCD are more susceptible to the happy face stimulus than the children with TD, leading to decreased performance in inhibition tasks.…”
Section: Discussionmentioning
confidence: 82%
“…Specifically, since inhibition contributed to an efficient performance of several executive function by allow the motor execution to be fluent and efficient [57], this cognitive function is essential for tasks that suddenly prevent one's self from executing an inappropriately prepared action such as riding a bicycle, playing dodge ball or football [58]. Deficits in this control process underline motor coordination problems [59]. For instance, additional taps in a motor inhibition test with children with DCD could reflect a deficit in motor control resulting in involuntary repetition of the taps of the same thumb [60].This assumption is in accordance with previous studies showing a global inhibition deficit in tasks that not requiring a motor response in DCD [61].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the mental state is immeasurable, our perception of an action depends on how similar the observed action with our internal repertoire of actions [5]. Individuals with a movement problem, such as Autism Spectrum Condition, usually find social interaction challenging due to diverging experiencing an action, hence different perception [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%